Medicinal Vascular Plants Traditionally Used for Treating Respiratory Ailments in Dereboğazı Village (Erzurum, Türkiye) - Bozkurt, Arzu Ergül (Fırat University, 2025)
This study was conducted to investigate the traditional medicinal plants used by local people in order to treat various types of respiratory disorders in Dereboğazı village (Erzurum). The present ethnomedical study was conducted in Dereboğazı (Palandöken, Erzurum - East Anatolia), between 2019-2020 years. Information on the ethnobotanical use of plant taxa were gathered through in-person interviews with Dereboğazı people and recorded using a questionnaire form. In order to gather ethnomedical data, 63 informants—16 men and 47 women—participated in the study. Samples of plants were prepared and placed in the Herbarium of Karadeniz Technical University Faculty of Forestry (KATO). This study reported 32 native and exotic vascular plant taxa from 13 families and 24 genera from Dereboğazı being ethnomedicinally used for treating various types of respiratory problems such as asthma, bronchitis, common cold, cough, flu and sore throat. The most common traditional method of using plants for therapeutic purposes is decoction (23 plant taxa). As a result of the study, the families with the highest number of plant taxa were Lamiaceae (9 taxa), Rosaceae (6), Asteraceae and Moraceae (3). The most commonly used plant parts by the local people were identified as aerial parts (13 taxa), fruits (8 taxa), leaves and dried fruits (7 taxa) and flowers (6 taxa). The present and similar studies, which include ethnomedical information on biological resources, will contribute to the field of pharmacy and medical science.

Bu çalışma, Dereboğazı köyünde (Erzurum) çeşitli solunum yolu rahatsızlıklarını tedavi etmek için yerel halk tarafından kullanılan geleneksel tıbbi bitkileri araştırmak amacıyla yapılmıştır. Bu etnomedikal çalışma 2019-2020 yılları arasında Dereboğazı'nda (Palandöken, Erzurum - Doğu Anadolu) gerçekleştirilmiştir. Bitki taksonlarının etnobotanik kullanımına ilişkin bilgiler Dereboğazı halkı ile yüz yüze görüşmeler yoluyla toplanmış ve bir anket formu kullanılarak kaydedilmiştir. Etnomedikal veri toplamak amacıyla çalışmaya 16 erkek ve 47 kadın olmak üzere 63 kişi katılmıştır. Bitki örnekleri hazırlanarak, Karadeniz Teknik Üniversitesi Orman Fakültesi (KATO) Herbaryumuna yerleştirilmiştir. Bu çalışmada, Dereboğazı'nda etnomedikal olarak astım, bronşit, soğuk algınlığı, öksürük, grip ve boğaz ağrısı gibi çeşitli solunum problemlerinin tedavisinde kullanılan 13 familya ve 24 cinse ait 32 yerli ve egzotik vasküler bitki taksonu tespit edilmiştir. Bitkilerin tedavi amaçlı kullanımında en yaygın geleneksel yöntem kaynatmadır (23 bitki taksonu). Çalışma sonucunda en fazla bitki taksonuna sahip familyalar Lamiaceae (9 takson), Rosaceae (6), Asteraceae ve Moraceae (3) olmuştur. Yerel halk tarafından en yaygın olarak kullanılan bitki kısımları toprak üstü kısımları (13 takson), meyveler (8 takson), yapraklar ve kurutulmuş meyveler (7 takson) ve çiçekler (6 takson) olarak tespit edilmiştir. Biyolojik kaynaklar hakkında etnomedikal bilgiler içeren bu ve benzeri çalışmalar eczacılık ve tıp bilimi alanına katkı sağlayacaktır.
Dereboğazı Köyünde (Erzurum, Türkiye) Solunum Rahatsızlıklarının Tedavisinde Geleneksel Olarak Kullanılan Damarlı Tıbbi Bitkiler
Keywords: Nonwood Forest Products Industry; Odun Dışı Orman Ürünleri Endüstrisi; Agricultural Engineering (Other); Ziraat Mühendisliği (Diğer)